2002
DOI: 10.4049/jimmunol.168.6.2720
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Immunity to Lymphoma Following Treatment with Anti-CD40 Monoclonal Antibody

Abstract: In this study we demonstrate that treatment with anti-CD40 mAb eradicates a range of mouse lymphomas (BCL1, A31, A20, and EL4), but only when used against i.v. tumor doses in excess of 107 cells. Only partial protection was seen against smaller tumor loads. We saw no evidence that anti-CD40 mAb changed the phenotype of the lymphomas or inhibited their growth in the initial period following treatment, but it did result in a rapid expansion of cytotoxic CD8+ cells that was able to clear the neoplastic disease an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 43 publications
2
65
0
Order By: Relevance
“…Interaction with its trimeric ligand on activated T cells results in APC activation, required for the induction of adaptive immunity (28,29). In preclinical models, rat anti-mouse CD40 mAb show remarkable therapeutic activity in the treatment of CD40 positive B cell lymphomas as well as various CD40-negative tumors (20,24,25). In our studies of therapeutic mAb, their potency is unprecedented, clearing bulk tumors from mice with established disease and providing immunity to rechallenge (20,24).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Interaction with its trimeric ligand on activated T cells results in APC activation, required for the induction of adaptive immunity (28,29). In preclinical models, rat anti-mouse CD40 mAb show remarkable therapeutic activity in the treatment of CD40 positive B cell lymphomas as well as various CD40-negative tumors (20,24,25). In our studies of therapeutic mAb, their potency is unprecedented, clearing bulk tumors from mice with established disease and providing immunity to rechallenge (20,24).…”
mentioning
confidence: 96%
“…Our work has focused on immunostimulatory anti-CD40 mAb (20,(23)(24)(25), which are also in clinical development (26,27). Reagents targeting this molecule have been investigated for .20 y and include both mAb and CD40L (20,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, the presence of these immunosuppressive factors might even result in alternative activated DCs that have acquired a strong T cell-tolerizing capacity after exposure to maturation stimuli. This could also explain the discrepancy between CD40 treatment of mice bearing s.c. tumors and AC tumors (26,34), as systemic anti-CD40 treatment in animals could perhaps not induce the desired maturation level of the eye-derived APC required for CTL induction, but rather an alternative activated DC endowed with the capacity to tolerize T cell responses. Because the unique microenvironment of the eye might prevent proper DC activation after CD40 ligation combined with the observation that AC tumor Ag can be presented to CTLs, it is tempting to speculate that neutralizing eye-derived APC-modulating cytokines will greatly improve immune intervention protocols.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that anti-CD40 treatment can be a very powerful method to improve tumor-specific CTL immunity in tumorbearing mice, leading to the eradication of otherwise lethal tumors (26,34). CD40 signaling has been shown to be a very powerful way to enhance tumor-specific immunity, most likely through the activation of DCs (35,36) that cross-present tumor Ags to CTLs, as also exemplified by the up-regulation of activation markers and costimulatory molecules on CD11c ϩ cells after administration of anti-CD40 Abs (data not shown) (37).…”
Section: Systemic Cd40 Activation Does Not Lead To Eradication Of Thementioning
confidence: 99%